TRANSFORMAÇÕES CONTEMPORÂNEAS E PERSPECTIVAS DO SERVIÇO SOCIAL NO MARANHÃO: incidência sobre o mercado de trabalho do assistente social e a questão da cultura profissional. - Josefa Batista Lopes (Universidade Federal do Maranhão, 2010)
Social Worker's incidence on the labor market and the rnatter of professional culture Abstraet: This paper considers social workers insertion in the professional work market considering Brazilian rnarkets reconfiguration that occurred due to the the impact of the changes that happened in the country with the implementation and consolidation of the nineties neoliberalism. The discussion about the theme is centered in two axis: a) the rnetamorphosis of the professional work market mainly from the second half of the 1990's, when there was a crossing process between the impacts of the 1988 Federal Constitution and the 1995 Brazilian State Reform and the processes that made work more flexible even though the State remains being the main employer; b) the inflections on the professional culture and in the movement of the profession's historie constitution considering the rnatter of professional identity.